2017
DOI: 10.1002/jpen.1036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Software Selection and ImageJ Tutorial Corrigendum on Skeletal Muscle Measures at the Third Lumbar Vertebra on Computed Tomography Scans in Clinical Populations

Abstract: Measures of skeletal muscle CSA at the L3 were found to be ∼1.53 cm higher with ImageJ than sliceOmatic. This difference was not found to affect interpretation against a published cut point. The importance of accounting for the ImageJ tutorial corrigendum was shown to be clinically significant when applied to published cut points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 20 publications
(57 reference statements)
1
30
1
Order By: Relevance
“…The slices with the clearest vertebral arch were determined to be retained for analyses. Image analysis for measuring CSA of the muscles was performed using ImageJ software [12]. Digital Imaging and Communications in Medicine format images were imported into ImageJ software and analyzed.…”
Section: Measurement Of Csa Of the Musclesmentioning
confidence: 99%
“…The slices with the clearest vertebral arch were determined to be retained for analyses. Image analysis for measuring CSA of the muscles was performed using ImageJ software [12]. Digital Imaging and Communications in Medicine format images were imported into ImageJ software and analyzed.…”
Section: Measurement Of Csa Of the Musclesmentioning
confidence: 99%
“…This abbreviated version also includes the final step that delineates the perimeter of the vertebral body and subtracts this measured value (cm 3 ) from the SM CSA obtained in steps 1–3 (Figure ). This final step yields a more accurate estimate of SM CSA as clearly shown by Teigen et al . This final step was published as a corrigendum after the original publication of the tutorial.…”
Section: Abbreviated Tutorial For Assessment Of Waist Circumference Amentioning
confidence: 76%
“…Additionally, Bland‐Altman plots suggested strong comparability between SliceOmatic and ImageJ for abdominal visceral fat and right‐thigh SM. Recently, 2 separate studies have compared the tutorial (with the corrigendum) for ImageJ with SliceOmatic . Van Vugt et al analyzed 50 randomly selected CT images and evaluated agreement of CSA analysis of various imaging programs including ImageJ (using the tutorial and corrigendum) and SliceOmatic .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the Slice‐O‐matic software rather than ImageJ software was most commonly used in previous studies, and different software programs may give slightly different results. A small sample study conducted by Teigen et al revealed that the skeletal muscle measures show excellent inter‐software agreement, thus the results of studies using different software programs may be compared reliably. Finally, our proposed cutoff values have not yet been applied in patient populations.…”
Section: Discussionmentioning
confidence: 99%